Does a Controlled Diet Improve Cellulite? - N.C, Marques,; J.L.M, Soares,; L.R.S, Guadanhim,; F.fa, Sternberg,; F.R, Picosse,; S, Yarak,; E, Bagatin, (International Journal of Nutrition, 2016)
Abstract: Several researchers have suggested that a targeted diet for reducing theadipose tissue may interfere with the severity of cellulite. Others emphasize that the diet composition seems to play a more relevant role than the calorie profile for weight loss and cellulite control. Objective: The aim of this study was to evaluate the influence of a controlled diet on body composition and cellulite improvement in adult women. Methods: Thirty two healthy women, aged from 25 to 40 were included. They receivedan orientation for a controlled diet to be followed for 3 months. Assessments were performed at the baseline and the end of the study which included four parameters: 1) Photonumeric cellulite severity scale; 2) Anthropometric measuremets 3) Skin elasticity (Cutometer®) and 4) Collagen density or echogenicity and length of the dermis-hypodermis interface line (ultrasonography - DermaScan®). The data was compared with the Paired T-test, Wilcoxon and Pearson's correlation for statistical analyses. Results: Only 14 completed the study. Although the scores of photonumeric scalereduced, there was no difference in the grade of cellulite severity. There were significant reductions in body measurement. The skin elasticity showed no significant change. On the other hand, the dermal density or echogenicity showed a significant increase in the right and left sides (p = 0.05 and p = 0.005, respectively); however, no difference was observed in the lenght of dermis-hypodermis line. Conclusion: the controlled diet was effective for the reduction of weight and body composition, but despite the increase in dermal collagen density, no clinical effect on cellulite could be detected.
Keywords: Diet; Cellulite; Carboydrate; Fat Mass; Loss Weight